People in glass houses ebook - Castle, Jayne (Harmony, 2024)
Two people desperate for answers wade through smoke and mirrors within the alien world of Harmony in this new novel by New York Times bestselling author Jayne Castle. His name is Joshua Knight. Once a respected explorer, the press now calls him the Tarnished Knight. He took the fall for a disaster in the Underworld that destroyed his career. The devastating event occurred in the newly discovered sector known as Glass House—a maze of crystal that is rumored to conceal powerful Alien antiquities. The rest of the Hollister Expedition team disappeared and are presumed dead. Whatever happened down in the tunnels scrambled Josh’s psychic senses and his memories, but he’s determined to uncover the truth. Labeled delusional and paranoid, he retreats to an abandoned mansion in the desert, a house filled with mirrors. Now a recluse, Josh spends his days trying to discover the secrets in the looking glasses that cover the walls. He knows he is running out of time. Talented, ambitious crystal artist Molly Griffin is shocked to learn that the Tarnished Knight has been located. She drops everything and heads for the mansion to find Josh, confident she can help him regain control of his shattered senses. She has no choice—he is the key to finding her sister, Leona, a member of the vanished expedition team. Josh reluctantly allows her to stay one night but there are two rules: she must not go down into the basement, and she must not uncover the mirrors that have been draped. But her only hope for finding her sister is to break the rules…